(untitled) (Politeja, 2015)
Many European citizens do not have a clear idea about European identity. But a European Dream (in many ways parallel to the American Dream) has raised hopes and offered opportunities for democratic and peaceful development. As F.J. Turner emphasized the importance of the frontier in shaping American character, we can also see the importance of the frontier in shaping the European mindset. In terms of topological mapping, a frontier is often also a war‑front. Outside Europe as well, borders such as the Great Wall of China have defined territory as a defended area. However, boundaries have seen not only war. Many cross‑border regions have in fact seen dialogue, communication, commerce, change, travel, and mutual inspiration. European identity was strengthened and defined through ancient reasoning concerning frontiers. According to Braudel, the Mediterranean cannot be understood independently from what is exterior to it. The first European identity was strengthened and defined on the frontier and the values of Europe are best perceived along its borders. The light shines strongest in the point of its source, but it is more appreciated to the point of its limit, where darkness and brightness compete for space – and even for life. European peripheries may be seen as a problem, yet they are the bastions of Europe and today, like yesterday, they have frequently prevented the institutional collapse of the center of Europe. Sometimes, an institutional breakdown begins at the peripheries and then, like an avalanche, sweeps the center away.